Between a Rock and a Hard Place: COVID Concerns and Partnered U.S. Mothers' Employment during the COVID-19 Pandemic. (November 2022) - Carlson, Daniel L.; Fielding-Singh, Priya; Petts, Richard J.; Williams, Kristi
Shutdowns of in-person school and childcare in spring 2020 in response to the coronavirus disease 2019 (COVID-19) pandemic were associated with substantial reductions in mothers' labor force participation (LFP). By fall 2020, in-person school and daycare were more widely available, but mothers' LFP remained as low as it was in spring. Coincidently, by fall 2020, daily COVID deaths had also began to peak. Using unique panel survey data from partnered U.S. mothers ( n = 263), the authors use structural equation modeling to analyze how mothers' concerns over COVID shaped their LFP in fall 2020. Findings show that mothers' COVID concerns were associated with reduced LFP via children's time at home, perceived stress, and remote work. Concerned mothers were more likely to keep children home, but this resulted in less paid work likely vis-à-vis work-family conflicts. The findings illuminate one reason mothers' LFP failed to rebound in fall 2020 despite increased access to in-person school and daycare.